Inorganic geochemical characterisation of the Velenje lignite in the representative P-9k/92 borehole profile (Slovenia) - Miloš Markič (Geologija, 2006)
The study is based on 30 lignite, 6 footwall and 3 hanging-wall interval samples. Lignite seam of the Pliocene age is 101 m thick in the treated profile.Minorelementgeochemistryis evaluated by the contents of 11 standard oxides, among which SiO2, Al2O3, Fe2O3 and CaO form the bulk composition. Trace-element characterization is based on contents of 46 elements. Stot., Ctot., Corg. and loss on ignition (LOI) at 1000 ˚C were analysed in addition. All analyses (by ICP-AES, ICP-MS, Leco) were carried out on the “whole lignite”/“whole rock” samples in the Acme Analytical Laboratories (Canada). Recalculation to the “pure inorganic matter” basis was carried out in order to obtain realistic relations between contentsof minor element oxides. Contents of the minor element oxides in the inorganic matter are dependant on the ash content, and, an ash content of 20-25 % was found out as an important “geochemical threshold”. SiO2 + Al2O3, together with positively corelated K2O and TiO2, increase with increasing ash content. On the contrary, CaO, MgO and Fe2O3, they increase with decreasing ash content. Affinity of organic binding of Ca,Mg,and(probably)of Fe is ascertained by negligible contents of Cinorg. Abundances of the great majority of trace elements are mostly lower and/or normal in comparison to the world coals. However, As, U, and Mo are typomorphic for the treated lignite. In spite of that, they are not critical. Widespread areas of different lithologies with higher contents of these elements are known throughout the world as well as in Slovenia.